PENGARUH TERPAAN TAYANGAN KONTEN YOUTUBE "TASYI MUKBANG & REVIEW TERBARU - INILAH BOBA TERENAK SE-INDONESIA" (Studi Pada Subscriber Tasyi Athasyia) - Jeihan Lutfiah Zahrani Yusuf, (2022)
In the current phenomenon, Youtube is the most widely used platform by the Indonesian people in the first half of 2021 (Results of the Jakpat Survey, 2021). The show entitled "Tasyi Mukbang & Latest Review - This is the Most Delicious Boba in Indonesia" attracted the attention of the audience with a total of 5.4 million viewers per 18/06/2022. This study aims to determine whether the content series "Tasyi Mukbang Battle" has an influence on the purchase decision of a product on the audience, and to find out how much influence it has. The theory used is uses and effects. Through correlation test, simple linear regression test, coefficient of determination test, and hypothesis testing, the researchers found the results of that there was an influence between the influence of the X variable, namely the exposure to the impressions of "Tasyi Mukbang & Battle - This is the Best Boba in Indonesia", and the Y variable, namely Buying decision. The magnitude of the influence of the X variable on the Y variable is 44.3%, it was also found in the regression test that the higher the exposure to the X variable, the greater the influence given to the Y variable. Keywords: Media Exposure, Mass Media Effect, Uses and Effect Theory